The Influence of Talent Management Practices on Employee Performance in Service-Based Organizations - Gautam, Ramesh Prasad (The Management Review, 2025)
Talent management is a strategic process focused on attracting, developing, retaining, and optimizing an organization’s workforce to achieve its goals efficiently. Within this framework, the study explores how talent management practices influence employee performance in the service sector of Surkhet District. This study employed a quantitative research approach, collecting survey data from 315 service sector employees in Surkhet District. Selected for its demographic diversity and role as the administrative capital of Karnali Province, the district’s workforce varies significantly in race, caste, age, gender, and marital status factors that often complicate the alignment of employee performance with organizational goals. This setting provided an ideal context for investigating the impact of talent management practices. Data was gathered through a structured questionnaire and analyzed using regression analysis in SPSS 25 to evaluate the relationship between talent management variables and employee performance. The results demonstrate a significant positive influence of key independent variables talent planning, talent development and attraction, recruitment and retention strategies, and rewarding and compensation systems on employee performance. These practices strengthen engagement, motivation, and productivity by implementing strategic workforce planning, fostering professional growth, optimizing hiring processes, and offering competitive rewards. Collectively, they contribute to enhanced organizational success. Service sector organizations face challenges in adopting strategic HR practices, including limited awareness, resource constraints, and a shortage of skilled professionals. Given the traditional emphasis on operational efficiency and the difficulties of managing workforce diversity, this study explores how talent management can enhance organizational performance in the region.